Quantitative Aspect of Phosphorylase (ab and a) in Ascaridia galli Collected from the Avian Host Gallus gallus domesticus - and Sanjay Shamrao Nanware, Govind Hanmantrao Balde (Recent Research in Science and Technology, 2011)
The phosphorylase (ab and a) metabolism in nematodes parasites shifts according to the availability of oxygen. Therefore, the study of phosphorylase (ab and a) metabolism is quite interesting not only from biochemical point of view but also from the point of view of chemotherapy as the number of metabolic steps increase, this may lead to an increase in the number of vulnerable points. In present communication the quantitative estimation of phosphorylase (ab and a) was done to understand the rate of glycogenolysis inÃ‚Â  Ascardia galli (schrank, 1788) Freeborn 1923 collected from the avian host Gallus gallus domesticus from Nanded region (M.S.) India.